PENGARUH PENGGUNAAN GADGET, MINAT BELAJAR DAN KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR SISWA KELAS XI IIS PADA MATA PELAJARAN EKONOMI DI SMAN 1 KEPANJEN - Zulfikar Adilla Sukarno; Prih Hardinto (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2018)
Learning process is the most important part because it determines how well the outcomes will be achieved by students. In the Learning process, there are some factors which influence. They are internal factor, external factor and exhaustion factor. But in this research only concern on internal factors: learning interest and emotional quotient and also external factor: gadget usage. The purpose of this research is to know the effect of gadget usage, learning interest and emotional quotient partialy and simultanously towards learning outcomes. The kind of this research is explanation research with quantitative approach. Data obtained by using quistioner and documentation. Questioners are given to the research samples by using technique proportional random sampling, the amount of the samples are 97. While documentation is used to obtain data about learning outcome at Economics Subject . The result of this research shows that there are significant effects of gadget usage, learning interest and emotional quotient towards learning outcomes. Each of independent variabel has significany effect such as: the effect of gadget usage is about 10,43%, the effect of learning interest is about 27,22% and the effect of emotional quotient is about 22,75%. DOI: https://dx.doi.org/10.17977/UM014v11i12018p009